1990
DOI: 10.1007/bf01796271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with simvastatin on plasma lipids and lipoproteins in patients with primary hypercholesterolemia

Abstract: We investigated long-term hypolipidemic effects and clinical safety of simvastatin, a new competitive inhibitor of 3-hydroxy-methylglutaryl coenzyme A reductase in 24 patients with familial and non-familial hypercholesterolemia. Patients received up to 40 mg simvastatin for a period of 30 months. Significant decreases were noted in plasma cholesterol (30%), plasma triglycerides (25%), very low density lipoprotein-cholesterol (26%), and low density lipoprotein-cholesterol (40%), whereas an increase in plasma hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…In our study, we found a larger decrease (45%), even though many of the subjects (19 out of 46) were taking lower doses of simvastatin. The greater fall we observed is in line with recent studies [17,18], confirming that simvastatin appears to be one of the most potent of the HMG-CoA reductase inhibitors [27].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, we found a larger decrease (45%), even though many of the subjects (19 out of 46) were taking lower doses of simvastatin. The greater fall we observed is in line with recent studies [17,18], confirming that simvastatin appears to be one of the most potent of the HMG-CoA reductase inhibitors [27].…”
Section: Discussionsupporting
confidence: 81%
“…We have confirmed that simvastatin induces potentially beneficial changes not only in LDL but in triglycerides and HDL [17][18][19][20][21], ancilliary actions that may play an important role in the clinical effectiveness of this drug. We have also shown that the increase in HDL is due to increases in both HDL 2 and HDL 3.…”
Section: Discussionsupporting
confidence: 54%
“…During the testing period, numerous side effects like diarrhea, obstipation, other gastrointestinal diseases, myositis, rhabdomyolysis, and others were observed [112]. As a result of the clarification of the connection between hypercholesterolemia and coronary heart disease, numerous studies have been carried out in recent years with various medications [113117]. With the introduction of selective and semiselective extracorporeal elimination methods for cholesterol, LDL, Lp(a), and triglycerides, all forms of previous therapy-resistant hypercholesterolemia can now be effectively treated [118].…”
Section: Ldl-apheresis Therapymentioning
confidence: 99%